Influence of eWOM to Purchase Intention Mediated by Trust and Comprehensive Review of Tenun Ikat Product on Instagram - Giltom Antonio Lenggu; Gede Ariadi (Management Analysis Journal, 2023)
The emergence of new communication channels and platforms due to the internet’s influence on social media and behaviour has created opportunities for creating and disseminating user-generated content. Nowadays, many companies turn over e-commerce to social media such as Instagram. The product of Tenun Ikat from East Nusa Tenggara (NTT) is promoted on Instagram, which makes the customer hesitate to buy the product. Additionally, scepticism, anxiety, and fear of social media content lead customers not to believe that the product can be trusted or not. By then, the researcher has established this paper using the fundamental theory of naïve that generates the mediated variable of comprehensive review and trust. This paper conceptualized how eWOM significantly impacts, if mediated by comprehensive review and trust, resulting in purchase intention. Analyzing sample data collection of 175 random customers who saw the promotion activity of Tenun Ikat NTT on Instagram achieved an outstanding result where comprehensive review has significant mediating the eWOM and purchase intention. This research shows that naïve theory is well contributed in this paper where it manages people to seek the detail of information, including personal experience, to pursue customer interest in the product. Theoretically, the study proves that the naïve theory has played a significant role in mediating comprehensive review and trust variables to pull out the critical aspect of eWOM and purchase intentions that benefit businesses.